Changes in liking for sweet and fatty foods following weight loss in women are related to prop phenotype but not to diet. Issue 9 (19th July 2016) - Burgess, Brenda; Rao, Salome P.; Tepper, Beverly J.
Abstract : Objective: Changes in perceived intensity and liking of tasted foods have not been studied during weight loss from dieting. These outcomes were examined during a 6‐month lifestyle intervention in women who had been classified by sensitivity to the bitter taste marker, 6‐n‐propylthiouracil (PROP), and then randomized to a low‐fat or low‐carbohydrate diet. Methods: Sixty‐nine women (BMI = 34.4 kg/m 2 ; age = 44.2 years) followed the low‐fat diet ( n = 31) or low‐carbohydrate diet ( n = 38). At baseline and at 3, and 6 months, they rated overall liking and intensity of attributes in strawberry milk and salad dressing varying in sucrose (0%, 15%, and 30% wt/vol) or fat (10%, 30%, 50% wt/vol) content, respectively. Results: Perceived intensity of the attributes did not change. For all participants, the 15% and 30% sucrose milk samples were equally liked at baseline and 3 months, but by 6 months, the 15% sucrose sample was highest liked ( P < 0.007). Also, the 50% fat sample was most liked at baseline and least liked by 6 months ( P = 0.04), and this effect was most pronounced in the nontasters ( P < 0.02). There were no effects of diet prescription on liking. Conclusions: Weight loss from dieting resulted in a hedonic shift for foods with lower sucrose and fat content.